Nutrition Management via Mini Farms to Prevent Stunting among 4–6 Year Olds - Sutinah; Anita Chandra Dewi Sagala; Ngatmini (Jurnal Ilmiah Pendidikan Profesi Guru, 2025)
Stunting is a chronic nutritional problem that continues to require comprehensive management in Indonesia, particularly in rural areas, despite a declining prevalence trend. Limited family nutrition literacy, low dietary diversity, and suboptimal utilization of local food resources place young children at risk of growth impairment. This study aimed to develop, examine, and critically evaluate a family-based nutrition management model through Mini Farms as a strategy for stunting prevention among children aged 4–6 years. The study employed a Research and Development approach using the ADDIE model with a one-group pretest–posttest design. Participants comprised ten children, two teachers, and ten parents from a rural early childhood education (PAUD) setting. Data were collected through expert validation questionnaires, practicality questionnaires, observations of Mini Farm implementation, pre- and post-intervention anthropometric measurements, and documentation. Research instruments included expert validation sheets, practicality questionnaires, observation checklists, and anthropometric measurement tools analyzed using WHO Z-score standards. Data analysis involved descriptive analysis to assess product validity and practicality and systematic comparison of conditions before and after the intervention. The findings indicate that the Mini Farm model meets good validity criteria and contributes to improved availability of fresh foods and strengthened family engagement. In conclusion, the Mini Farm model is considered feasible, practical, and potentially effective as a family nutrition management strategy for stunting prevention.